2015
DOI: 10.1038/nrurol.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on best practice management regarding the use of intravesical immunotherapy with BCG for bladder cancer

Abstract: | Multiple clinical trials have demonstrated that intravesical Bacillus Calmette-Guérin (BCG) treatment reduces recurrences and progression in patients with non-muscle-invasive bladder cancer (NMIBC). However, although BCG has been in use for almost 40 years, this agent is often underutilized and practice patterns of administration vary. This neglect is most likely caused by uncertainties about the optimal use of BCG, including unawareness of optimal treatment schedules and about patient populations that most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 122 publications
0
101
0
5
Order By: Relevance
“…In fact, patients who have papillary disease recurrence at the 3-mo evaluation are often referred to as “BCG refractory,” although some experts have suggested that to be considered truly unresponsive to BCG as the disease should have been treated with at least one additional 3-wk course of BCG [9]. Nonetheless, patients with papillary recurrence after induction BCG at the 3-mo cystoscopic evaluation present a treatment quandary, as well as being a matter of discussion during clinical trial designs in the BCG failure population.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients who have papillary disease recurrence at the 3-mo evaluation are often referred to as “BCG refractory,” although some experts have suggested that to be considered truly unresponsive to BCG as the disease should have been treated with at least one additional 3-wk course of BCG [9]. Nonetheless, patients with papillary recurrence after induction BCG at the 3-mo cystoscopic evaluation present a treatment quandary, as well as being a matter of discussion during clinical trial designs in the BCG failure population.…”
Section: Discussionmentioning
confidence: 99%
“…[31] BCG there is, once again, the potential for a global shortage with regards to this crucial, lifesaving therapy for bladder cancer. [33] Kamat et al [34] reported the "Expert Consensus Document" that provides a comprehensive review of immunomodulatory therapy with BCG, recommends best practice guidelines to improve overall use and patient outcomes (Table 1). However, the definitions of the terms BCG relapse, BCG-refractory and BCG-intolerant were described in Table 2.…”
Section: Predictive Markers Of Nmibcmentioning
confidence: 99%
“…However, the definitions of the terms BCG relapse, BCG-refractory and BCG-intolerant were described in Table 2. [34] Peer-review: This manuscript was prepared by the invitation of the Editorial Board and its scientific evaluation was carried out by the Editorial Board. …”
Section: Predictive Markers Of Nmibcmentioning
confidence: 99%
“…But even in the case of BCG treatment for NMIBC patients, many issues remain under question: the appropriate schedule to reduce recurrence and progression without increasing adverse events [94][95][96]; the reason why a proportion of patients do not respond to BCG treatment; the detail description of immune mechanism which could permit to predict the response to the treatment; the possibility of using other mycobacteria species that have shown similar or increased effective than BCG but with potential increased safety; etc. In fact, the experience using mycobacteria in BC is permitting novel approaches for improving its efficacy.…”
Section: Future Perspectives: a Long History With Room For Improvementmentioning
confidence: 99%